Çocuklarda inme etiolojisinde doğal inhibitör eksikliği: Üç olgu sunumu - (:unkn) unknown (My University, 2007)
Çocukluk çağında inme ender görülmekle birlikte önemli bir hastalık ve ölüm nedenidir. Etiolojik nedenler erişkinlerden oldukça faklıdır. Geçmiş yıllarda çocuklarda inmelerin yaklaşık yarısında etioloji saptanırken, son yıllarda doğal inhibitör eksikliklerinin tanınmasıyla, kalıtsal trombofililerin inme etiolojisindeki yeri ve önemi daha iyi anlaşılmıştır. Etiolojiyi bilmek, seyir ve alevlenmeyi öngörmek açısından önem kazanmaktadır. Bu yazıda doğal inhibitör eksikliği saptanan üç olgu sunularak çocuklarda serebrovasküler hastalık etiolojisinde kalıtsal trombofililerin önemi, tedavisi ve profilaksisi tartışıldı.

Stroke, a rare condition during childhood, remains to be an important cause of mortality and morbidity. The etiology of stroke in children is different from adults and could be determined only in the half of the cases previously. However, hereditary thrombophilias and coagulation defects have been more commonly identified during last two decades and the importance of the hereditary thrombophilias in the etiology of stroke is better understood. Clarifying the etiology is important to predict the prognosis and prevent recurrences. We report here three patients with hereditary thrombophilias leading stroke and discuss the importance as well as the treatment and prophylaxis of hereditary thrombophilias.
Hereditary thrombophilla as stroke aetiology in children: Three case report
Keywords: Pediatri